Efektivitas LKPD Berbasis RME terhadap Kemampuan Pemahaman Konsep Ditinjau dari Ketuntasan Belajar - Meika, Ika; Solikhah, E. Fidri Firdaushi; Yunitasari, Ika; Sujana, Asep (SJME (Supremum Journal of Mathematics Education), 2023)
This research is a continuation of the article Development of Trigonometric Material Teaching Materials through the RME Approach (Meika et al., 2023). Before the teaching materials that have been developed are used, it is necessary to know in advance the effectiveness of the teaching materials. Therefore, it is necessary to trial the use of these teaching materials in a class to determine their effectiveness. The purpose of this study is to determine the effectiveness of RME-based LKPD on the ability to understand concepts in terms of learning completeness. The method used is Design Based Research (DBR) with the Plomp development model consisting of three stages, namely: Preliminary Research, Prototyping Stage and Assessment. This article contains the results of the assessment phase. At the assessment stage, a final test was carried out and filled out a student response questionnaire to determine the effectiveness of the LKPD that had been developed. The effectiveness of LKPD is seen from the completeness of student learning outcomes. The final test results showed that the average score of class X Science 1 was 78 with three students who did not complete KKM. KKM Madrasah Aliyah Mathla'ul Anwar Menes Centre is 71. The percentage of students who achieved completion was 85.72%. Therefore, LKPD products have been effective in developing students' ability to understand mathematical concepts. The results of the student response questionnaire showed that the average percentage of all aspects assessed was 77.87% with the category "Good".